Peran Just Energy Transition Partnership (JETP) dalam Transisi Energi Indonesia untuk Mendukung Pencapaian SDG 13 Tahun 2022-2025 - Mentari Sandrina Al Khalifi; Hasna Wijayati (Socio-political Communication and Policy Review, 2026)
Indonesia's heavy reliance on fossil fuels, particularly coal which accounts for over 62 percent of national electricity generation, renders energy transition an urgent priority within the framework of global climate commitments. This study aims to analyze the mechanism and implementation of JETP in supporting Indonesia's energy transition, evaluate its contribution to SDG 13 achievement, and identify factors influencing its effectiveness during the 2022–2025 period. Employing a qualitative literature review method with thematic analysis of ten relevant scientific sources, this study finds that JETP with a financing commitment of USD 20 billion makes significant contributions through five strategic investment areas driving decarbonization of the power sector. Nevertheless, the dominance of loan-based financing, with grants comprising only 1.37 percent of total funds, risks creating new fiscal burdens and deepening Indonesia's technological dependency on developed nations. JETP's effectiveness in accelerating SDG 13 achievement is further constrained by regulatory inconsistencies, resistance from fossil fuel industry stakeholders, and limited adaptive governance capacity. This study concludes that structural reforms in financing architecture and strengthened inclusive governance are absolute prerequisites for JETP to genuinely realize a just and sustainable energy transition in Indonesia.